2013
DOI: 10.1111/mmi.12370
|View full text |Cite
|
Sign up to set email alerts
|

The Schizosaccharomyces pombe fusion gene hal3 encodes three distinct activities

Abstract: SummarySaccharomyces cerevisiae Hal3 and Vhs3 are moonlighting proteins, forming an atypical heterotrimeric decarboxylase (PPCDC) required for CoA biosynthesis, and regulating cation homeostasis by inhibition of the Ppz1 phosphatase. The Schizosaccharomyces pombe ORF SPAC15E1.04 (renamed as Sp hal3) encodes a protein whose amino-terminal half is similar to Sc Hal3 whereas its carboxyl-terminal half is related to thymidylate synthase (TS). We show that Sp Hal3 and/or its N-terminal domain retain the ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 69 publications
0
19
1
Order By: Relevance
“…Surprisingly, this gene also showed a 3= fragment with sequence homology to thymidylate synthase-encoding genes. The authors resequenced the genomic locus of S. pombe and that of the related yeast Schizosaccharomyces japonicus and confirmed the unusual structure of the gene in both cases (99). The same authors also showed that the S. pombe Hal3 protein or even its N-terminal domain could rescue an S. cerevisiae cab3 single mutant or hal3 vhs3 double mutant, indicating that this protein is sufficient to achieve PPCDC activity.…”
Section: Hal3 From Schizosaccharomyces Pombe Is a Moonlighting Proteimentioning
confidence: 77%
See 2 more Smart Citations
“…Surprisingly, this gene also showed a 3= fragment with sequence homology to thymidylate synthase-encoding genes. The authors resequenced the genomic locus of S. pombe and that of the related yeast Schizosaccharomyces japonicus and confirmed the unusual structure of the gene in both cases (99). The same authors also showed that the S. pombe Hal3 protein or even its N-terminal domain could rescue an S. cerevisiae cab3 single mutant or hal3 vhs3 double mutant, indicating that this protein is sufficient to achieve PPCDC activity.…”
Section: Hal3 From Schizosaccharomyces Pombe Is a Moonlighting Proteimentioning
confidence: 77%
“…In an interesting evolutionary study, the same group examined the properties of the corresponding protein in the fission yeast S. pombe (99). Although there has been some controversy about the precise location of S. pombe on the fungal evolutionary tree (100), it is clear that the ancestors of S. cerevisiae and S. pombe separated quite early, with estimations ranging between 420 and 330 million years ago (101).…”
Section: Hal3 From Schizosaccharomyces Pombe Is a Moonlighting Proteimentioning
confidence: 99%
See 1 more Smart Citation
“…The visible-UV absorption profile of recombinant CnHal3a and CnHal3b devoid of the GST tag was obtained in a Nanodrop ND1000. Cross-linking of recombinant CnHal3b was carried out as in (Molero et al , 2013), except that 0.01% glutaraldehyde was used. Evaluation of disordered regions in the Cryptococcus proteins was done using the Genesilico MetaDisorder server (Kozlowski and Bujnicki, 2012) and the IUPred software (Dosztanyi et al , 2005).…”
Section: Assay Of Protein Phosphatase Activitymentioning
confidence: 99%
“…However, whereas both CaHal3 and CaCab3 retained their predicted PPCDC‐related functions, only CaCab3 exhibited phosphatase regulatory potential in vivo, suggesting that in C. albicans CaCab3, but not CaHal3, acts as a moonlighting protein (Petrényi et al , ). Other fungal genomes present interesting structural alternatives, such as that of fission yeast, in which a likely gene fusion event generated a single gene product (SpHal3), composed of an N‐terminal PPCDC core, including a short acidic tail, followed by a functional C‐terminal thymidylate synthase domain (Molero et al , ). SpHal3 is a functional PPCDC but exhibits limited capacity to inhibit ScPpz1 or the S. pombe homolog Pzh1 in vitro .…”
Section: Introductionmentioning
confidence: 99%